2017
DOI: 10.1097/pas.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent BRAF Gene Rearrangements in Myxoinflammatory Fibroblastic Sarcomas, but Not Hemosiderotic Fibrolipomatous Tumors

Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) is a low grade soft tissue sarcoma with a predilection for acral sites, being associated with a high rate of local recurrence but very infrequent distant metastases. Although a t(1;10) translocation resulting in TGFBR3-MGEA5 fusion has been reported as a recurrent genetic event in MIFS, this abnormality is seen only in a subset of cases. As no studies to date have investigated the spectrum of alternative genetic alterations in TGFBR3-MGEA5 fusion negative MIFS, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 39 publications
4
39
1
Order By: Relevance
“…The French Sarcoma Group found such amplicons in 19/404 (5%) sarcomas analyzed with genomic arrays; amplification‐positive tumors were primarily diagnosed as UPS and dedifferentiated liposarcomas and none as MIFS, HFLT, or PHAT . In addition, array‐ and FISH‐based studies have identified VGLL3 amplification as a recurrent feature (70%‐80% of the cases) in both HFLT and MIFS, including cases with BRAF rearrangement . The present study thus confirms that an amplicon in 3p11‐12, correlating with increased expression of VGLL3 is a highly recurrent feature of MIFS, irrespective of whether a t(1;10) or a BRAF fusion is present or not.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The French Sarcoma Group found such amplicons in 19/404 (5%) sarcomas analyzed with genomic arrays; amplification‐positive tumors were primarily diagnosed as UPS and dedifferentiated liposarcomas and none as MIFS, HFLT, or PHAT . In addition, array‐ and FISH‐based studies have identified VGLL3 amplification as a recurrent feature (70%‐80% of the cases) in both HFLT and MIFS, including cases with BRAF rearrangement . The present study thus confirms that an amplicon in 3p11‐12, correlating with increased expression of VGLL3 is a highly recurrent feature of MIFS, irrespective of whether a t(1;10) or a BRAF fusion is present or not.…”
Section: Discussionsupporting
confidence: 80%
“…MIFS with or without the t(1;10) have also been shown to display loss of material from chromosome arm 3p and amplification of a ~1.5 Mb sequence in chromosome bands 3p11‐12; the amplicon includes the genes VGLL3 , CHMP2B , and POU1F1 , of which only the former two showed increased expression . Frequent amplification of VGLL3 in both MIFS and HFLT was confirmed by others using FISH . However, VGLL3 amplicons, and corresponding overexpression, have been detected also in other types of, typically high‐grade, sarcoma (eg, myxofibrosarcoma, undifferentiated pleomorphic sarcoma [UPS], and de‐differentiated liposarcoma), some of which were negative for the t(1;10) and some had an unknown t(1;10) status …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In another study done by Movva et al 2539 sarcomas were profiled by IHC, FISH/CISH, NGS and Sanger sequencing and none harbored a BRAF mutation . Notably, BRAF fusions have been detected in few sarcomas (non‐chondrosarcomatous), as reported by Kao et al On the other hand, BRAF mutation has not yet been reported in chondrosarcoma. Therefore, with regards to our patient, BRAF mutation in the cartilaginous component supports the interpretation of melanocytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the breadth of assay coverage, novel fusion partners and completely novel fusion genes will invariably be incidentally identified in the course of routine clinical practice . As our nascent understanding of sarcomagenesis evolves, it is important to take this opportunity to rigorously evaluate cases, and to share this information through the literature and databases.…”
Section: Introductionmentioning
confidence: 99%